Output distributions and topic maps of safety related journals. (February 2016) - Li, Jie; Hale, Andrew
Abstract: This paper presents topic maps of six core safety journals, based on analysis of 13, 028 articles published in those journals as downloaded from the Web of Science. Bibliometric mapping methods were used to visualize the map of the topics covered in each journal. Analysis was also made of the changes in topics over time. The results show that safety science research in those journals has grown very rapidly over the last half century, with USA as the most productive in total and also in each year in the period. The topic clusters of these journals reveal the focus of each journal, which may be determined by the dominant methodologies used, the activity whose safety is studied or the object of study (e.g. workplace, safety management, regulation, etc.). The different journals also show regional differences in the papers they attract. The field in total is highly multidisciplinary. The topics of Safety Science have been focused on major hazard, transportation and work safety; Journal of Safety Research divides its attention between work and traffic safety, with a smaller cluster on statistics; Accident Analysis and Prevention is concerned almost exclusively with road safety; Injury Prevention is concerned mainly with injury mechanisms, but includes topics not treated by the other 5 journals, such as violence, suicide and other intentional injury and child safety at school and in the home. Reliability Engineering and System Safety and the Journal of Loss Prevention in the Process Industries focus mainly on major hazard, with the latter most concerned with the technology of failure mechanisms and the former on quantitative risk assessment.